2018
DOI: 10.1038/s41396-018-0312-9
|View full text |Cite|
|
Sign up to set email alerts
|

Selective colonization ability of human fecal microbes in different mouse gut environments

Abstract: Mammalian hosts constantly interact with diverse exogenous microbes, but only a subset of the microbes manage to colonize due to selective colonization resistance exerted by host genetic factors as well as the native microbiota of the host. An important question in microbial ecology and medical science is if such colonization resistance can discriminate closely related microbial species, or even closely related strains of the same species. Using human-mouse fecal microbiota transplantation and metagenomic shot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 88 publications
4
41
0
Order By: Relevance
“…There are several documented regimens for depleting gut bacteria in mice with antibiotics 26,27,28,29,30,31 . We chose our cocktail of antibiotics due to their known capacity to target a broad range of bacteria in the gut and because we found several examples of successful bacterial depletion in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…There are several documented regimens for depleting gut bacteria in mice with antibiotics 26,27,28,29,30,31 . We chose our cocktail of antibiotics due to their known capacity to target a broad range of bacteria in the gut and because we found several examples of successful bacterial depletion in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was no significant difference between the individuals caught in the wild or fed on a controlled diet across two time periods. Several factors can influence the success of colonization by exogenous microbes and the presence of a native microbiota offering resistance is one of the main lines of defense, especially in the case of hosts with high diversity communities 69 , as may be the case in this study. In addition, we acknowledge that an investigation of the effects of the individuals caught in the wild or fed on a controlled diet requires a greater understanding of the composition of the wild diet of the two colonies that were sampled here, but there is little data on the general biology of this omnivorous species, which further increases the importance of the 18S rRNA data from the present study.…”
Section: Found That Formentioning
confidence: 74%
“…Their immunodeficiency may contribute to their pre-existing low diversity gut microbiome status before human fecal material transplant. In a study by Zhou et al, NSG and C57BL6/J mice whose native microbiota were depleted by antibiotics followed by FMT had no significant differences in diversity but did observe significant differences in which species colonized[39]. A study done by Ericsson et al showed that it is easier to transfer high diversity fecal donor samples into low diversity recipients, which could help to explain the success of engraftment and stability in our model[30].…”
Section: Discussionmentioning
confidence: 91%